2021
DOI: 10.3390/diagnostics11122193
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of the BZ COVID-19 Neutralizing Antibody Test for the Culture-Free and Rapid Detection of SARS-CoV-2 Neutralizing Antibodies

Abstract: Rapid and accurate measurement of SARS-CoV-2 neutralizing antibodies (nAbs) can aid in understanding the development of immunity against COVID-19. This study evaluated the diagnostic performance of a rapid SARS-CoV-2 nAb detection test called the BZ COVID-19 nAb test BZ-nAb (BZ-nAb; BioZentech). Using the 90% plaque-reduction neutralization test (PRNT-90) as a reference, 104 serum specimens collected from COVID-19-positive and -negative patients were grouped into 40 PRNT-90-positive and 64 PRNT-90-negative spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Some of them have high costs, require trained personnel, and can only be carried out in a Biosafety Safety Level 3-equipped laboratory, whereas others, such as the cPass surrogate virus neutralization test (sVNT) (GenScript, Piscataway, NJ, USA) used in this work, are ELISA-based assays and only require optical density readers. The development of immunocapture-based rapid diagnostic tests that determine the levels of neutralizing antibodies in serum and/or whole capillary blood provides an inexpensive, simple, and highly portable tool that could be helpful on a large scale and, outside of the lab, in immuno-surveillance settings ( 13 15 ). In this study, we aimed at investigating the antibody response of a large cohort of individuals who received different types of vaccines in terms of anti-RBD antibody titer and neutralizing activity, measured with both an sVNT and a rapid test.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them have high costs, require trained personnel, and can only be carried out in a Biosafety Safety Level 3-equipped laboratory, whereas others, such as the cPass surrogate virus neutralization test (sVNT) (GenScript, Piscataway, NJ, USA) used in this work, are ELISA-based assays and only require optical density readers. The development of immunocapture-based rapid diagnostic tests that determine the levels of neutralizing antibodies in serum and/or whole capillary blood provides an inexpensive, simple, and highly portable tool that could be helpful on a large scale and, outside of the lab, in immuno-surveillance settings ( 13 15 ). In this study, we aimed at investigating the antibody response of a large cohort of individuals who received different types of vaccines in terms of anti-RBD antibody titer and neutralizing activity, measured with both an sVNT and a rapid test.…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Jung et al - using a different immunochromatographic assay - showed fair agreement (Kappa: 0.91) between cPass ELISA and BZ-nAb. However, the methods were performed 0-2 months after SARS-CoV-2 natural infection ( Jung et al, 2021 ). In contrast, a study by Saker et al showed sensitivity between 49.2-66.7% and specificity between 68.4-77.3% of a qualitative immunochromatographic method (Dynamiker Biotechnology) compared to quantitative ELISA (TECO) ( Saker et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In currently used detection methods, PRNT 50 is a criterion standard for verifying the nAb, which was first used to detect neutralizing antibodies in 2014. Although it has higher accuracy and sensitivity than other tests, such as hemagglutination and many commercial enzyme immunoassays, the main disadvantage is that it takes days to get results [ 10 , 15 , 18 , 22 , 32 ]. In addition, because live viruses are used while conducting PRNT 50 , it requires extremely strict operating procedure and high requirements for biosafety level and personnel operations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, which is a semi-quantitative detection method and the first surrogate neutralization assay to be commercially available. However, both methods mentioned above have difficulties, such as maintaining virus viability, biosafety level 3 (BSL 3) laboratory requirement, and being time-consuming to reveal the result [ 19 22 ].…”
Section: Introductionmentioning
confidence: 99%